2010
DOI: 10.1093/aje/kwq089
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Intake and Risks of Rheumatoid Arthritis and Systemic Lupus Erythematosus in Women

Abstract: Antioxidants may protect against development of rheumatoid arthritis or systemic lupus erythematosus by combating oxidative stress. The authors identified and confirmed incident cases of rheumatoid arthritis and systemic lupus erythematosus among 184,643 US women followed in the Nurses' Health Study and Nurses' Health Study II cohorts in 1980-2004. Semiquantitative food frequency questionnaires assessed intakes of vitamins A, C, and E and a-carotene, b-carotene, b-cryptoxanthin, lycopene, lutein, and zeaxanthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 46 publications
(47 reference statements)
2
59
1
2
Order By: Relevance
“…In similar lines of thought, these results on dietary items as risk factors for developing RA may be explained by sodium intake and may partly explain why these associations have not been detected in all studies and that some studies report contradictory results [4,5,[7][8][9]27].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In similar lines of thought, these results on dietary items as risk factors for developing RA may be explained by sodium intake and may partly explain why these associations have not been detected in all studies and that some studies report contradictory results [4,5,[7][8][9]27].…”
Section: Discussionmentioning
confidence: 69%
“…Historically, diet has received considerable attention as a potential risk factor. Although studies have suggested associations, mainly regarding fruit, vegetables, meat and disease development, the results have been inconclusive [4][5][6][7][8][9][10]. Regarding the consumption of alcohol, recently published meta-analyses concluded that moderate consumption of alcohol intake is inversely associated with the development of RA [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant intake, including vitamins A, C, and E, α-carotene, β-carotene, β-cryptoxanthin, lycopene, lutein, and zeaxanthin, was not associated with the risk of developing SLE. 24 Inability to generalize results outside of Caucasian females is a limitation of the vitamin D and antioxidant intake studies due to the demographics of those enrolled in the Nurses’ Health Study.…”
Section: Dietary Influences On Slementioning
confidence: 99%
“…Patients' characteristics, such as age and gender, can affect the individual capacity to prevent oxidative stress ; thus, the study should require not only an enrollment of both sexes but also a sex-gender analysis. Very recently, a meta-analysis that assessed the intake of vitamin A, vitamin C, vitamin E, alpha-carotene, beta-carotene, beta-cryptoxanthin, lycopene, lutein, and zeaxanthin in women from foods and supplements suggested that antioxidant intake is not associated with the risk of developing either rheumatoid arthritis or systemic lupus (Costenbader et al, 2010). The above results indicate that caution should be used in designing interventional trials and that the availability of baseline information on major potential confounding factors and extrapolating data obtained from men to women.…”
Section: Micronutrients: Vitamins and Mineralsmentioning
confidence: 99%